The Implementation Musnad Ilaih in Communication and Its Impct in The Interpretation of the Qur’an - Saiful Amri; Aulia Fitri (International Journal of Research, 2024)
This article aims to extrapolate the effect of using musnad ilaihi in establishing effective communication from the perspective of ma'ni science and the impact of musnad Ilahi in the interpretation of Qur'anic verses. This study used a qualitative approach as it aimed to narrate and analyze the effect of musnad ilaihi in Qur'anic and Hariam communication and its contribution to the interpretation of Qur'anic verses. The results of this study indicate that musnad ilaihi as part of the study of Qur'anic balaghah has a contribution in interpreting the verses of the Qur'an as in the use of QS.Al Insyirah verses 5-6 which explain the use of musnad ilaihi to explain if both arem nakirah, then the meaning of the second ism nakirah is different from the meaning of the first ism nakirah.